1944
DOI: 10.1002/bjs.18003112314
|View full text |Cite
|
Sign up to set email alerts
|

Fractures of the triquetrum

Abstract: THE concentration of attention on the navicular has caused the other bones of the wrist to be neglected. We would like to rectify this in the case of the triquetrum, and emphasize the fact that fracture of this bone is commonly misdiagnosed as fracture of the posterior pole of the lunate. Bohler, quoting Schnek's statistics, first brought this latter diagnosis into prominence. In our opinion he exaggerated its frequency, isolated fracture of the posterior pole of the lunate being very rare, and only seen by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

1968
1968
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 0 publications
1
19
0
2
Order By: Relevance
“…3 Bonin and Greening described a fracture of the triquetrum in association with a perilunate dislocation and a fracture of the proximal pole of the scaphoid. 1 Weseley and Barenfeld described a case of trans-scaphoid, trans-capitate, trans-triquetral perilunate fracture dislocation of the wrist. 17 Both closed and open reduction of fracture dislocations of the carpal bones have been practiced in the past.…”
Section: Discussionmentioning
confidence: 98%
“…3 Bonin and Greening described a fracture of the triquetrum in association with a perilunate dislocation and a fracture of the proximal pole of the scaphoid. 1 Weseley and Barenfeld described a case of trans-scaphoid, trans-capitate, trans-triquetral perilunate fracture dislocation of the wrist. 17 Both closed and open reduction of fracture dislocations of the carpal bones have been practiced in the past.…”
Section: Discussionmentioning
confidence: 98%
“…First, it was accepted that body fractures occurred with compression mechanism and dorsal chip fractures occurred with avulsion mechanism [2] [3], but afterwards it had been suggested that dorsal chip fracture of the triquetrum was caused by the effect of ulnar styloid [1] [4] or the hamate [5] on the dorsum of the os triquetrum upon a fall on the wrist in dorsiflexion.…”
Section: Discussionmentioning
confidence: 99%
“…Wrist injuries occurring after a fall on the wrist account for an important portion of daily clinical practice of orthopedics. Although triquetrum fractures causing ulnar-sided wrist pain are the second most common carpal fractures after scaphoid, they are less common seen in daily clinical practice [2] [4] [5]. Most of these fractures are seen after a fall on an outstretched hand and they clinically manifest with painful and edematous wrist and limitation in movement [2] [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[46][47][48][49][50][51] Dorsal triquetral fractures can occur with a fall forward onto a palmar flexed hand or backward onto a dorsiflexed hand. [46][47][48][49] There are 2 leading theories regarding the cause of dorsal triquetral fractures. One theory suggests that the fracture results as an avulsion injury from dorsal capsular ligaments, 46,47 whereas the other suggests that the fracture is a result of a chisel action caused by an elongated ulnar styloid process.…”
Section: Triquetrummentioning
confidence: 99%